2020
DOI: 10.3389/fnagi.2020.592212
|View full text |Cite
|
Sign up to set email alerts
|

Various Diseases and Clinical Heterogeneity Are Associated With “Hot Cross Bun”

Abstract: Objective: To characterize the clinical phenotypes associated with the “hot cross bun” sign (HCBs) on MRI and identify correlations between neuroimaging and clinical characteristics.Methods: Firstly, we screened a cohort of patients with HCBs from our radiologic information system (RIS) in our center. Secondly, we systematically reviewed published cases on HCBs and classified all these cases according to their etiologies. Finally, we characterized all HCBs cases in detail and classified the disease spectra and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 45 publications
0
35
0
1
Order By: Relevance
“…Studies by our group and other researchers have suggested that neuroinflammation is of considerable importance in the pathologic process of PD (4)(5)(6)(7)(8)(9)(10)(11)(12). In PD, neuroinflammatory cells are composed of hyperplastic reactive glial cells, especially microglia and astrocytes, the essential components of the neurovascular unit (NVU) (13).…”
Section: Introductionmentioning
confidence: 98%
“…Studies by our group and other researchers have suggested that neuroinflammation is of considerable importance in the pathologic process of PD (4)(5)(6)(7)(8)(9)(10)(11)(12). In PD, neuroinflammatory cells are composed of hyperplastic reactive glial cells, especially microglia and astrocytes, the essential components of the neurovascular unit (NVU) (13).…”
Section: Introductionmentioning
confidence: 98%
“…Parkinson’s disease (PD) is a highly prevalent neurodegenerative disorder worldwide with characteristic motor dysfunctions including bradykinesia, stiffness and resting tremor ( Tolosa et al, 2021 ). Ours and other studies have indicated that some indicators such as neuroinflammatory, neuroimaging mediators and serum neurofilament light chain are usually applied as markers in diagnosing and evaluating the progression and severity of PD and PD Syndromes ( Wang et al, 2020 , 2021 ; Yang et al, 2020 ; Zhu et al, 2020 , 2021a ; Bestwick et al, 2021 ; Liu et al, 2021 ; Quadalti et al, 2021 ). Identifying potential biomarkers for early diagnosis and assessment is one of the research hotspots in the field of PD ( Avenali et al, 2020 ; Papuć and Rejdak, 2020 ; Ma et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive impairment, including impairment in attention, executive function, memory, speech, and visual perception, is a common and salient manifestation of Parkinson's disease (PD) and interferes with the ability to perform activities of daily living and patient outcomes 1–6 . Our recent studies have demonstrated various neuroimaging markers and their relative neuropathogenesis in PD and PD Syndromes (PDS), which appear to contribute to motor/non‐motor dysfunctions and discriminative aspects 7–12 . According to the degree of cognitive impairment, 13,14 PD patients can be classified into those with PD with normal cognition (PD‐NC), PD with mild cognitive impairment (PD‐MCI), and PD with dementia (PDD).…”
Section: Introductionmentioning
confidence: 99%